Implementasi Manajemen Rantai Pasok Produksi Kue Bolu Pada UMKM Bolu Ira - Tanjung, Lailatul Syifa; Sari, Resy Kumala; Yusmita, Yesi; Aliza, Nur; Hasibuan, Alfi Syahrin (Journal of Social and Community Service, 2024)
Abstract UMKM Bolu Kak Ira is one of the micro, small and medium enterprises engaged in the production of sponge cakes in Kampar Regency. Even though they have quality products, these MSMEs face challenges in managing an efficient and effective supply chain, especially in dealing with fluctuations in demand and managing raw materials. This community service program aims to implement integrated supply chain management in Bolu Kak Ira UMKM, in order to increase operational efficiency and market competitiveness. Activities carried out include initial analysis of supply chain conditions, preparation of inventory management strategies, human resource training, and implementation of simple information technology for stock monitoring and control. The results of this program show increased efficiency in managing raw materials, reduced operational costs, and increased customer satisfaction. Apart from that, Bolu Kak Ira UMKM are able to respond to changes in market demand more quickly and accurately. Through this program, it is hoped that Bolu Kak Ira UMKM can continue to develop and contribute more to the local economy, as well as becoming an example for other UMKM in implementing effective supply chain management.